2014
DOI: 10.1002/glia.22675
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic transforming growth factor-beta signaling reduces subacute neuroinflammation after stroke in mice

Abstract: Astrocytes limit inflammation after CNS injury, at least partially by physically containing it within an astrocytic scar at the injury border. We report here that astrocytic transforming growth factor-beta (TGFβ) signaling is a second, distinct mechanism that astrocytes utilize to limit neuroinflammation. TGFβs are anti-inflammatory and neuroprotective cytokines that are upregulated subacutely after stroke, during a clinically accessible time window. We have previously demonstrated that TGFβs signal to astrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(127 citation statements)
references
References 73 publications
5
110
0
1
Order By: Relevance
“…Other studies have demonstrated increased expression of TGF␤ (Lehrmann et al, 1998;Martinez et al, 2001;Doyle et al, 2010;Pál et al, 2012) and its receptor (Pál et al, 2014) after stroke, mostly in macrophages (Lehrmann et al, 1998;Martinez et al, 2001;Doyle et al, 2010). TGF␤ has been shown to suppress excessive neuroinflammation during the subacute phase after brain ischemia, as evidenced by decreased expression of the proinflammatory microglia/macrophage markers CD68 and iNOS (Cekanaviciute et al, 2014), and is also able to directly inhibit LPSmediated activation of microglia (Kim et al, 2004;Le et al, 2004). Zhou et al (2012) recently demonstrated that TGF␤ enhances IL-4-induced alternative activation of microglia by strongly increasing the expression of Ym1.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated increased expression of TGF␤ (Lehrmann et al, 1998;Martinez et al, 2001;Doyle et al, 2010;Pál et al, 2012) and its receptor (Pál et al, 2014) after stroke, mostly in macrophages (Lehrmann et al, 1998;Martinez et al, 2001;Doyle et al, 2010). TGF␤ has been shown to suppress excessive neuroinflammation during the subacute phase after brain ischemia, as evidenced by decreased expression of the proinflammatory microglia/macrophage markers CD68 and iNOS (Cekanaviciute et al, 2014), and is also able to directly inhibit LPSmediated activation of microglia (Kim et al, 2004;Le et al, 2004). Zhou et al (2012) recently demonstrated that TGF␤ enhances IL-4-induced alternative activation of microglia by strongly increasing the expression of Ym1.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytic transforming growth factor-beta (TGF-β) is anti-inflammatory and a neuroprotective cytokine that is upregulated after stroke. In mice with TGF-β signaling specifically inhibited in astrocytes, photothrombotic motor cortex stroke leads to excessive inflammation, infarct expansion and worse motor outcome (Cekanaviciute et al , 2014). These data suggest that reactive astrocytes play an essential role in neuroprotection by limiting inflammation in the peri-infarct cortex and preserve brain function during the subacute period after stroke.…”
Section: Astrocytes In Neuroprotectionmentioning
confidence: 99%
“…11 TGFß, which is associated with the M2-like microglial reaction, is often regarded as an anti-inflammatory cytokine, and indeed, antagonizing TGFß signaling in models of adult stroke exacerbates lesion size. 12,13 However, other studies in the literature reveal TGFß to have a complicated and sometimes paradoxical effect upon CNS injury resolution. For example, in experimental autoimmune encephalomyelitis, inhibiting TGFb1 signaling reduced T-cell infiltration and reduced the severity of disease.…”
Section: Introductionmentioning
confidence: 99%